(untitled) (Eurasian Research Bulletin, 2025)
In this paper, we study silver, copper, and gold nanoparticles stabilized with natural biopolymers chitosan, sodium alginate, and gelatin using infrared spectroscopy (IR). The interaction of the biopolymer functional groups with the surface of metal nanoparticles obtained by the "green synthesis" method was studied. The obtained IR spectra showed a shift of the bands corresponding to the stretching vibrations of the OH, -H, and C=O groups, indicating the formation of coordination bonds between the metal atoms and the active centers of the polymers. It was found that the efficiency of nanoparticle stabilization depends on the chemical nature of the biopolymer, as well as on the pH and reaction temperature. Additional methods, UV spectroscopy and dynamic light scattering (DLS), confirmed the formation of stable nanocomposites with a particle size of 20-80 nm. The results demonstrate that biopolymers can act as both a reducing agent and a stabilizer, ensuring the environmentally friendly synthesis of metal nanoparticles. The obtained materials are promising for use in biomedicine, catalysis, and sensorics.